Morphometric characterization of the Carrizal basin applied to the evaluation of flash floods hazard, San Juan, Argentina - Esper Angillieri, María Yanina (2012)
The Carrizal river basin is located to the northwest of San Juan Province in the Iglesia department. One of the main geological hazards that affect the Iglesia department is flash floods, produced by heavy seasonal rains, characterized by their high velocities and destructive power. The Carrizal river basin was selected as a test case to evaluate the potential magnitude of flash floods in relation to their associated hazard level. This paper evaluates some of the hydrological aspects of a torrential regime of Carrizal basin that can cause severe damage like the event that took place in the area during February 1944. Various morphometric characteristics of the Carrizal river basin were analysed in order to evaluate its flash ﬂood hazard. For this purpose, the basin was divided into five sub-basins, according to lithological aspects, and some basic measurements (surface, perimeter, basin length, river beds, elevations and slope of the main river bed, and of a number of minor river beds) were calculated. These measurements allowed predicting approximately the behaviour of the basin in the presence of a series of theoretical rainstorms that may generate unusual runoff volumes. The predicted flash floods were compared against the Carrizal flash flood.